Parotid Sialolithiasis complicated by Streptococcus Pneumoniae infection - Faisal, Ummu Salamah; Zainulabid, Ummu Afeera; Ramli, Ramliza (Elsevier, 2023)
Staphylococcus aureus is the most common cause of suppurative parotitis, while pneumococcal parotitis is one of the least common and least recognized causes. Here, we share a case of left parotid abscess caused by Streptococcus pneumoniae with underlying sialolithiasis.